Analyzing the Efficiency of County Road Production – Evidence from Eastern German Counties1. Issue 4 (9th July 2018) - Fritzsche, Carolin
Abstract: This study analyzes the efficiency of the road production by local governments using data envelopment analysis. The production of roads is a costly public service, which makes an efficiency analysis in this field an interesting subject. I enhance the previous literature, first, by examining the differences in the efficiencies of eastern German counties while considering the deformation of the pavement and foundation of roads, which previous studies have not included due to data limitations. Second, I use a unique dataset on road quality for my efficiency analysis and show that the efficiency levels differ from those in studies that apply proxies, such as the number of accidents, to capture the quality of roads. These findings indicate that there is a great need to develop reliable variables to describe government services. Additionally, I show that the correlations between efficiency levels and county characteristics vary greatly depending on the quality indicator used.